Private thoughts: in two parts complete ... - Beveridge, William (Robert Carter, 1839)
Part I. Upon religion, digested into twelve articles : to which are added, forty practical resolutions, formed upon the foregoing articles -- Part II. Upon a Christian life : or, necessary directions for its beginning and progress on earth, in order to its final perfection in the beatific vision.